A Novel Alginate-Based Delivery System for the Prevention and Treatment of Pressure-Overload Induced Heart Failure - Ambrish Kumar; Marwa Belhaj; Donald J. DiPette; Jay D. Potts (Frontiers Media S.A., 2021)
Background: α-CGRP (alpha-calcitonin gene related peptide) is a cardioprotective neuropeptide. Our recent study demonstrated that the administration of native α-CGRP, using osmotic mini-pumps, protected against transverse aortic constriction (TAC) pressure-induced heart failure in mice. However, the short half-life of peptides and the non-applicability of osmotic pumps in humans limits the use of α-CGRP as a therapeutic agent for heart failure (HF). Here, we sought to comprehensively study a novel α-CGRP delivery system using alginate microcapsules to determine its bioavailability in vivo and to test for cardioprotective effects in HF mice.Methods: Native α-CGRP filled alginate microcapsules (200 µm diameter) were prepared using an electrospray method. The prepared alginate-α-CGRP microcapsules were incubated with rat cardiac H9c2 cells, mouse cardiac HL-1 cells, and human umbilical vein endothelial cells (HUVECs), and the cytotoxicity of the alginate-α-CGRP microcapsules was measured by a trypan-blue cell viability assay and a calcium dye fluorescent based assay. The efficacy of the alginate-α-CGRP microcapsules was tested in a TAC-pressure overload mouse model of heart failure. Male C57BL6 mice were divided into four groups: sham, sham-alginate-α-CGRP, TAC-only, and TAC-alginate-α-CGRP, and the TAC procedure was performed in the TAC-only and TAC-alginate-α-CGRP groups of mice to induce pressure-overload heart failure. After 2 or 15 days post-TAC, alginate-α-CGRP microcapsules (containing an α-CGRP dose of 6 mg/kg/mouse) were administered subcutaneously on alternate days, for 28 days, and echocardiography was performed weekly. After 28 days of peptide delivery, the mice were sacrificed and their hearts were collected for histological and biochemical analyses.Results: Our in vitro cell culture assays showed that alginate-α-CGRP microcapsules did not affect the viability of the cell lines tested. The alginate-α-CGRP microcapsules released their peptides for an extended period of time. Our echocardiography, biochemical, and histology data from HF mice demonstrated that the administration of alginate-α-CGRP microcapsules significantly improved all cardiac parameters examined in TAC-mice. When compared to sham mice, TAC significantly decreased cardiac functions (as determined by fraction shortening and ejection fraction) and markedly increased heart and lung weight, left ventricle (LV) cardiac cell size, cardiac apoptosis, and oxidative stress. In contrast, the administration of alginate-α-CGRP microcapsules significantly attenuated the increased heart and lung weight, LV cardiac cell size, apoptosis, and oxidative stress in TAC mice.Conclusion: Our results demonstrate that the encapsulation of α-CGRP in an alginate polymer is an effective strategy to improve peptide bioavailability in plasma and increase the duration of the therapeutic effect of the peptide throughout the treatment period. Furthermore, alginate mediates α-CGRP delivery, either prior to the onset or after the initiation of the symptom progression of pressure-overload, improves cardiac function, and protects hearts against pressure-induced HF.